Profile of the production engineer student at a school of engineering in Brazil: academic and professional trajectories and tendencies - Inoue, Alan Pultrini [UNESP]; Jabbour, Ana Beatriz Lopes de Sousa [UNESP]; Jabbour, Charbel José Chiappetta [UNESP] (My University, 2012)
The objective of this paper is to introduce a study on the academic trajectory and professional profile of production engineers who graduated in a traditional and renowned Brazilian University (School of Engineering at Bauru – FEB). The study was conducted with the first three classes of undergraduates in the production engineering program at FEB/UNESP. A 50% response rate was obtained and with the data collected it was possible to characterize the professional profile of the students and outline their academic trajectory. According to the sample, the main result is that the curricular grid is the main criterion of similarity in student education, thus, the focus on program improvements should focus on the curricular grid. Tendencies are also pointed out to guide the search for improvements in the academic trajectory of production engineering students.
Keywords: Production engineering; Complementary education; Engineer profile